(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The heart is the central organ responsible for maintaining vital activity in the human body and ensuring the balance of the circulatory system. Cardiovascular diseases such as hypertension, heart failure, and arrhythmias are widespread, and pharmacotherapy plays a crucial role in their treatment. This article analyzes drugs affecting cardiac function, their mechanisms of action, clinical applications, and adverse effects. The main goal is to study the impact of these medications on heart function in depth, determine their significance in medicine, and provide a foundation for future research.